Subsecond Changes in Top Down Control Exerted by Human Medial Frontal Cortex during Conflict and Action Selection: A Combined Transcranial Magnetic Stimulation Electroencephalography Study - Taylor, Paul C. J; Nobre, Anna C; Rushworth, Matthew F. S (The Journal of neuroscience, 2007)
Action selection requires choosing one of all the possible conflicting action plans that are available. There is currently a debate as to whether the dorsal medial frontal cortex (dMFC) merely detects or actively resolves response conflict. We used combined on-line transcranial magnetic stimulation and electroencephalographic recording (TMS–EEG) to test whether human dMFC plays a critical causal role in conflict resolution, and whether the mechanism for such a function is via interactions with primary motor cortex. In an Eriksen flanker task, subjects discriminated the direction of the centermost arrow in an array of five, responding with the left or right hand. The lateralized readiness potential (LRP), a measure of relative levels of activity in left and right motor cortices, was also recorded. Reaction times and error rates were higher on incongruent than congruent trials, and incongruent trials produced a positive LRP deflection reflecting initial partial activation of the incorrect response. On one-half of trials, repetitive TMS was applied to left dMFC starting 100 ms before visual stimulus onset and ending 100 ms afterward. TMS disrupted performance by selectively increasing error rates on contralateral (right hand) incongruent trials. TMS also only modulated the LRP on incongruent trials, causing an increased positive deflection (associated with preparation of the incorrect response) starting 180 ms after visual stimulus onset. TMS of a control site did not interfere with behavior or motor cortical activity. dMFC has a direct causal role in resolving conflict during action selection, and the mechanism involves the top–down modulation of primary motor cortical activity.